Potential agronomic and environmental benefits of neem coated urea (NCU) application in rice (Oryza sativa L.) - A systematic review: Benefits of NCU application in rice - Surekha, K; Pragnya, M; Manasa, V; Gobinath, R; Brajendra, P (ORYZA-An International Journal of Rice, 2025)
In the year 2015, the Indian Government mandated that all domestic urea producers apply a neem coating to their products. This measure aimed to enhance nitrogen use efficiency and mitigate NO3- leaching. In this review paper, application of neem-coated urea (NCU) in rice cultivation has been extensively studied for its impact on grain yield, nitrogen use efficiency (NUE), nitrification inhibition (NI), ammonical nitrogen (NH4-N) concentration in soil, methane (CH4) emissions, nitrous oxide (N2O) emissions, and ammonia (NH3) loss. Numerous researchers have reported increased grain yield and NUE with NCU application, attributing it to enhanced panicle and grain numbers, and reduced N release rates. Both neem cake and neem oil formulations have shown superiority over uncoated urea, with neem cake generally exhibiting a higher impact on yield and NUE. The effect of NCU on yield was significant at lower N application rates, with clay soils showing the greatest yield increase. The NCU has demonstrated significant nitrification inhibition (NI), leading to reduced NO3-N concentration in soil, with neem oil being more effective than neem cake. NCU has also been effective in retaining NH4-N in soil, particularly at optimum concentrations and has shown promise in reducing CH4 and N2O emissions, especially under aerobic conditions. NCU has been effective with high clay content in retaining NH4-N in soil, reducing N2O emissions and reducing the NH3 loss through volatilization. Overall, the NCU application presents a promising approach to enhance rice productivity while mitigating greenhouse gas emissions and improving N utilization efficiency, although further research is warranted to fully understand its effects on greenhouse gas emissions, NH3 loss and to optimize application practices.